INVESTIGASI TERSANGKA VEKTOR CHIKUNGUNYA DI KABUPATEN OGAN KOMERING ULU TIMUR TAHUN 2009 - Ambarita, Lasbudi Pertama; Sitorus, Hotnida (Publikasi Penelitian Terapan dan Kebijakan, 2011)
Investigations of chikungunya vectors suspect was held follow-up the report from Health Office of East OKU District and Puskesmas (health center) Batumarta VIII. Many peoples from Madang Suku III Sub District have clinical symptomps similar to chikungunya. The major symptomps were fever, headache, arthralgia and skin rash. This investigation aims to determine the mosquito larvae indices (house index, breteau index, container index and angka bebas jentik), larval species and the habitat types of vector suspect. Observations of larvae/pupae of Aedes wasconducted in 2 villages of Madang Suku III Sub District. The methods of survei using standard methods of larval survey (Ministry of Health, 2002). A total of 200 houses were surveyed in both villages. Larval index (house index, breteau index, container index and angka bebas jentik)obtained from Bina Amarta village were 56%, 87, 23,7% and 44% respectively, while in Wanabakti village the larval index were 50%, 76, 25,3% and 50% respectively. Of Aedes genus, Ae. albopictus larval was predominantly found in both villages. Ae. albopictus larvae were found most in drums, concrete â€bakâ€ and buckets. It is strongly suspected if the suspect vector in these two villages is Ae. albopictus.